Experimental american trypanomiasis in rats: sympathetic denervation, parasitism and inflammatory process Desnervação simpática, parasitismo e processo inflamatório durante a doença de Chagas experimental, em ratos - Conceição R. S. Machado; Antonio L. P. Ribeiro (Memorias do Instituto Oswaldo Cruz, 1989)
Tissue parasitism, inflammatory process (histologic methods) and sympathetic denervation (glyoxylic acid-induced histofluorescence for demonstration of catecholamines) were studied in the heart (atrium and verntricle) and the submandibular gland of rats infected with the Y strain of Trypanosoma cruzi. In the heart paralleling intense parasitism and inflammatory process, the sympathetic denervation started at day 6 of infection and at the end of the acute phase (day 20) practically no varicose nerve terminals were found in both myocardium and vessels. In the submandibular gland, in spite of the rarity of anastigote pseudocysts and the scarcity of inflammatory foci, slight to moderate (days 13-15 of infection) or moderate to severe denervation (day 20) was found. At day 120 of infection both organs exhibited normal pattern of sympathetic innervation and only the heart showed some inflammatory foci and rare psudocysts (ventricle). Our data suggest the involvement of circulating factors in the sympathetic denervation phenomena but indicate that local inflammatory process is, at least, an aggravating factor. Parasitismo tecidual, processo inflamatório (métodos histológicos) e desnervação simpática (histofluorescência induzida por ácido glioxílico para demosntração de catecolaminas) foram estudados no coração (átrio e ventrículo) e na glândula submandibular de ratos infectados com cepa Y de Trypanosoma cruzi. No coração, em paralelo com intenso parasitismo e processo inglamatório, a desnervação simpática iniciuo-se no 6º dia de infecção e ao fim da fase aguda (20º dia) praticamente nenhuma terminação nervosa varicosa foi encontrada tanto no miocárdio como em vasos. Na glândula submandibular, apesar da raridade de ninhos de amastigotas e da escassez de focos inflamatórios, encontram-se discreta e moderada 13º-15º dia de infeccção) ou moderada a severa (20º dia) desnervação. Aos 120 dias de infecção, ambos os órgãos exibiram padrão normal de inervação e somente o coração mostrou alguns focos inflamatórios e raros pseudocistos (ventrículos). Nossos dados sugerem o enlvolvimento de fatores circulantes no fenômeno de desnervação simpática mas indicam que processo inflamatório local é, pelo menos, um fator agravante.